Profil Character Strengths dari Tiap Jenis Celebrity Worship Penggemar K-Pop - Ayesha Mahardzika Nurul Islami; Susandari (Bandung Conference Series: Psychology Science, 2022)
Abstract. The phenomenon “The Korean Wave or Hallyu Wave” brings people to know the term of K-Pop. Fans of K-Pop are often revealed as a form of worship or Celebrity Worship. Fan behavior towards idols can be assessed in various ways, ranging from reasonable behavior to unreasonable behavior. This can have an impact on the lives of the fans themselves and those around them. This study aims to look at the Character Strengths of each type of celebrity worship by fans K-Pop. This study uses a quantitative approach using descriptive methods. The sampling technique in this research is non probability sampling with convenience sampling. The subjects of this study amounted to 610 respondents. The measuring instrument used is Celebrity Attitude Scale by McCutcheon (2002) which has been adapted into Indonesian by Efathania & Aisyah (2019) and Values in Action–Inventory Strength by Peterson & Seligman (2004) which has been adapted into Indonesian by Akmal (2008). The result of this study indicate that fans K-Pop in Indonesia belong to the intense-personal. Profiles character strengths that stand out in all types of celebrity worship show the same result of the strengths, i.e kindness, open-mindedness, appreciation of beauty and excellent, and fairness. While the character strengths that are less prominent in all types also show the same result, i.e. bravery, leadership, self-regulation, and humility. Abstrak. Fenomena Korean Wave atau Hallyu Wave mengantarkan masyarakat mengenal istilah K-pop. Perilaku yang ditampilkan oleh para penggemar K-pop ini sering diungkap sebagai bentuk dari pemujaan atau Celebrity Worship. Perilaku penggemar terhadap idola dapat dinilai beragam, dimulai dari perilaku yang wajar sampai yang tidak wajar. Hal ini dapat berdampak kepada kehidupan penggemar itu sendiri maupun orang lain di sekitarnya. Penelitian ini bertujuan untuk melihat profil Character Strengths setiap jenis celebrity worship pada penggemar K-pop. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan metode deskriptif. Teknik sampling yang digunakan pada penelitian ini adalah non-probability sampling dengan teknik convenience sampling. Subjek penelitian berjumlah 610 responden. Alat ukur yang digunakan yaitu Celebrity Attitude Scale dari McCutcheon (2002) yang diadaptasi ke dalam Bahasa Indonesia oleh Efathania & Aisyah (2019) dan Values In Action–Inventory Strength dari Peterson & Seligman (2004) yang telah diadaptasi ke dalam Bahasa Indonesia oleh Akmal (2008). Hasil penelitian ini menunjukkan penggemar K-Pop di Indonesia mayoritas tergolong ke dalam jenis intense-personal. Profil character strengths yang menonjol pada keseluruhan jenis celebrity worship menunjukkan hasil yang sama yaitu kindness, open-mindedness, appreciation of beauty and excellent, dan fairness. Sedangkan character strengths yang kurang menonjol pada keseluruhan jenis juga menunjukkan hasil yang sama, yaitu bravery, leadership, self-regulation, dan humility.